Uticaj socijalnih i monetarnih doznaka dijaspore na društvo i privredu matice: slučaj Srbije - Filipović, Jovan; Milosavljević, Zoran; Ruso, Jelena (Sociološki pregled, 2022)
The paper provides an overview of both social and monetary diaspora remittances and their societal and economic impacts. Since migration is never a sole “muscle drain” (labor power drain), but always to a certain extent a “brain drain”, the study analyzes possible effects of high-skilled international migration (highly-skilled diaspora). In addition, the pros and cons of monetary remittances are summarized and analyzed. Being among the countries with the largest Diasporas relative to the total nation’s population, Serbia represents a rich case study for societal and economic impacts of social and monetary diaspora remittances.
Keywords: socijalne doznake; monetarne doznake; društveni uticaji; ekonomski uticaji; visokokvalifikovana srpska dijaspora